Analisis Rentabilitas Berbasis Laporan Keuangan BRI Syariah Tahun 2013–2015 - Abdul Haris Romdhoni (ITB AAS INDONESIA Surakarta, 2016)
This study aims to examine the profitability of financial ratios. Profitability became quite urgent, because the profitability is the ability of a company to generate profit with the capabilities of the BRI Syariah. It was often a problem in some companies or banks. Profitability for the Year 2013-2015 BRI Syariah good enough for the performance of this study dipenghujung BRI Syariah able to improve its financial performance either ROA, ROE, net income margin and operating expenses.Keywords: profitability, financial ratios and financial performance.